An analysis on the current situation of energy development and its environmental problems in Yulin City - Xiaowei Zhai; Zhuo Cheng; Shaohai Chang; Xiaofei Ai; Xiongzhe Zhang (Energy Reports, 2020)
This paper has done research on the current situation of energy development and its problems in Yulin for improving the coordinated development between economy and ecological environment. Through the current situation analysis of the principal energy development and environmental pollution, it is found that the industrial "three wastes" come mainly from the derivatives of the energy development and utilization process, and the enterprises with the biggest amount of industrial waste are from the energy industry, of which the extensive development and utilization of principal energy is one of the main reasons for the high emission load of industrial "three wastes". Combined with the Environmental Kuznets Curve Theory, it is found that the EKC of industrial wastewater discharge is in the shape of inverted "N", while the EKC of industrial exhaust and solid wastes discharge are in the shape of "N". In order to realize the coordinated development of energy development and environment, it should pay attention to the classification and collection of industrial wastewater as well as the transformation of treatment mode in the future development, promote biological technology to control industrial exhaust from terminals, and strengthen the utilization of main industrial solid wastes at the same time.
Keywords: 330; Energy development and utilization; Environmental Kuznets Curve; Environmental quality; Industrial "three wastes"; Yulin City